Green Technology Opportunities and Challenges in Sustainable Marine Logistics - Andi Sitti Chairunnisa (Collaborate, 2024)
The maritime logistics sector plays an important role in supporting global trade, but also contributes to significant greenhouse gas emissions and environmental impacts. To overcome these challenges, the adoption of green technologies is becoming increasingly important in achieving sustainable maritime logistics. This research aims to explore the opportunities and challenges of implementing green technology in the maritime logistics industry. Through literature studies, interviews with stakeholders, and case studies, this research identifies three main opportunities, namely reducing emissions and environmental impacts, operational efficiency and cost savings, as well as regulatory compliance, and improving company reputation. However, significant challenges were also identified, including high initial investment costs, lack of supporting infrastructure, regulatory barriers, and limited incentives. To overcome this challenge, collaboration between government, industry, financial institutions, and civil society is needed to develop a comprehensive regulatory framework, provide incentives, and facilitate investment in supporting infrastructure. Further research is also needed to analyze the environmental impacts and life cycle costs of different green technologies, as well as explore innovative business models and funding strategies. The transition towards green and sustainable maritime logistics is not only important to preserve the environment, but also to ensure long-term economic and social sustainability.